Kontradiksi Keberlanjutan Usaha Ekonomi Kreatif Masyarakat di Kampung Purun Kota Banjarbaru - Noor Syafitri; Ismar Hamid (Prodi Sosiologi FISIP ULM, 2023)
The people in Kampung Purun, Kota Banjarbaru, depend on creative economic activities based on purun plants. This study aims to analyze the sustainability of the purun plant-based creative economy in the midst of the existence of a diamond mining company in Kampung Purun, Banjarbaru City. This study uses a qualitative approach with a case study type of research. Data collection techniques using participant observation, in-depth interviews and documentation. The results of the study show that creative economic activities through purun woven which the people of Kampung Purun began to develop in 2016 were able to have a positive impact on the community's economy, namely increasing the community's income sources. Purun woven has been highlighted by various parties and circles, one of which is the Banjarbaru City Government which provides support and training for craftsmen to be able to develop purun woven products. Until now there are seven galleries in Purun Village, which accommodate the results of community purun woven. However, behind the progress and success of purun woven-based creative economic activities in Purun Village, there is a big problem regarding its sustainability. Sustainability is on the brink due to the depletion of sources of raw materials (purun plants). The craftsmen do not have their own land for planting purun, making it difficult for the craftsmen to meet the demand for purun raw materials. It was compounded by the fact that the locations where students took purun were in the area of a diamond mining company. This fact made the purun-based creative economy in Kampung Purun even more threatened.